2010
DOI: 10.1038/nature08833
|View full text |Cite
|
Sign up to set email alerts
|

RAF inhibitors prime wild-type RAF to activate the MAPK pathway and enhance growth

Abstract: Activating mutations in KRAS and BRAF are found in more than 30% of all human tumours and 40% of melanoma, respectively, thus targeting this pathway could have broad therapeutic effects. Small molecule ATP-competitive RAF kinase inhibitors have potent antitumour effects on mutant BRAF(V600E) tumours but, in contrast to mitogen-activated protein kinase kinase (MEK) inhibitors, are not potent against RAS mutant tumour models, despite RAF functioning as a key effector downstream of RAS and upstream of MEK. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

135
1,385
7
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,479 publications
(1,568 citation statements)
references
References 31 publications
135
1,385
7
16
Order By: Relevance
“…19 This mechanism might have clinical implications because promoted dimerization of CRAF and BRAF could lead to resistance to RAF inhibitors. 20,21 In this study, we report a novel complex BRAF mutation, BRAF V600delinsYM , identified in 4 out of 492 Japanese PTC cases (0.81%). We also performed its functional characterization, and it showed constitutively active kinase function and transforming ability, suggesting that it is a new PTC oncogene that activates the MAPK signaling pathway as does BRAF V600E .…”
mentioning
confidence: 76%
“…19 This mechanism might have clinical implications because promoted dimerization of CRAF and BRAF could lead to resistance to RAF inhibitors. 20,21 In this study, we report a novel complex BRAF mutation, BRAF V600delinsYM , identified in 4 out of 492 Japanese PTC cases (0.81%). We also performed its functional characterization, and it showed constitutively active kinase function and transforming ability, suggesting that it is a new PTC oncogene that activates the MAPK signaling pathway as does BRAF V600E .…”
mentioning
confidence: 76%
“…This work was essential in identifying MEK as being of particular importance in BRAF-inhibitor resistance and, thus, the potential synergy between BRAF and MEK inhibitors 55 . The mechanistic specificity of this work additionally led to the description of a phenomenon dubbed 'paradoxical activation' of the MAPK pathway via BRAF inhibition in BRAF-wild-type cells, for example, keratinocytes [56][57][58][59] . This discovery suggested that some of the hyperproliferative cutaneous manifestations associated with BRAF inhibition in the clinic might be mitigated by combination therapy incorporating a MEK inhibitor.…”
Section: Braf-targeted Therapiesmentioning
confidence: 99%
“…Furthermore, as this inhibitor is only effective on cells transformed by this V600E mutation, another BRaf-specific inhibitor, GSK2118436, which targets the V600K mutation, is also in a small phase III trial having shown great potential in patients with brain metastases 81 . However some caution remains as the inhibition of the BRaf mutation V600E (and also V600K by GSK2118436) with these BRaf inhibitors has been shown in some patients to reactivate the MAPK pathway through CRaf 82,83 , and developing resistance to BRaf inhibitors is a problem.…”
Section: Current Therapies In the Treatment Of Metastatic Melanomamentioning
confidence: 99%